Combination Immunotherapy with 4-1BBL and CTLA-4 Blockade for the Treatment of Prostate Cancer. (24th October 2011) - Youlin, Kuang; Li, Zhang; Xiaodong, Weng; Xiuheng, Liu; Hengchen, Zhu
Abstract : Immune regulation has been shown to be involved in the progressive growth of some murine tumours. Interruption of immune regulatory pathways via activation of 4-1BB or cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) blockade appears to be a promising strategy for cancer immunotherapy. In this study, we examined the effectiveness of 4-1BBL-expressing tumor cell vaccine in combination with CTLA-4 blockade on rejection of murine prostate cancer RM-1. We found that the combination of both a vaccine consisting of 4-1BBL-expressing RM-1 cells and CTLA-4 blockade resulted in regression of RM-1 tumors and a significant increase in survival of the tumour cell recipients, compared to that of either treatment alone. The combined vaccination resulted in higher CTL against RM-1 cells and increased secretion of IFN-γ, TNF-α, and IL-2 in the mix-cultured supernatant. These results suggest that combining activation of 4-1BB and blockade of CTLA-4 may offer a new strategy for prostate cancer immunotherapy.